IMPLEMENTASI KURIKULUM MERDEKA MELALUI PENDAMPINGAN FASILITATOR PADA PROGRAM SEKOLAH PENGGERAK DI KABUPATEN GARUT - Mudrikah, Achmad; Didin Wahidin; Yana Heryana (LPPM UNINUS, 2024)
Implementation of the Kurikulum Merdeka is a curriculum development policy implemented by the Ministry of Education and Culture for students' learning in schools. The development carried out is in the form of a variety of extra-curricular learning through optimizing content so that students have enough time to explore concepts and improve competencies. Implementation of the curriculum by schools has begun to be implemented in 2021, namely by the first-generation Sekolah Penggerak as many as 2,499 schools throughout Indonesia. The number of schools assisted in this activity were 5 elementary schools in the Garut district, SDN 1 Jayaraga, SDN 1 Lebak Agung, SDN 4 Bagendit, SD IT Cokro Aminoto, and SD IT Alam Garut. To succeed in implementing the curriculum in the five Sekolah Penggerak, 5 types of interventions were carried out consisting of consultative and asymmetrical assistance; strengthening school human resources; learning with a new paradigm; data-driven planning; and digitalization of schools. Facilitators tasked with assisting principals, teachers and school supervisors, aim to realize a student-centered school. To achieve this goal, the method applied to the assistance of the five schools in the driving school program is Participatory Action Research (PAR). This method was developed in the form of: 1) Encouraging collaboration across the school education ecosystem and stakeholders in the district; 2) Developing a Community of Principal Practitioners, Teachers, and School Supervisors; 3) Developing the competence of Principals, Teachers, and School Supervisors; 4) Monitoring the learning progress of the Principal, School Supervisor, and Teachers. The results of the implementation of mentoring activities indicate that the strengthening of the resources of school principals, teachers, and school supervisors in implementing the implementation of an independent curriculum has been achieved; achieving an understanding of the new learning paradigm; the need for increased understanding of data-based planning and school digitization Keywords: Kurikulum Merdeka, Sekolah Penggerak, Facilitator, Elementary Schools